The role of nuklear Malaysia as a hybrid organisation to promote science culture: a study using Triple Helix Model / Bashillah Baharuddin ... [et al.] - Baharuddin, Bashillah; Yusof, Mohd Hafizal; Mat Sali, Siti Syarina; Adnan, Habibah (UiTM Press, 2024)
This research paper investigates the Malaysian Nuclear Agency’s (Nuklear Malaysia) role as a Hybrid Organisation in promoting a scientific culture to help Malaysia achieve its vision of becoming a developed, high-income nation. The analysis focuses on two primary activities led by Nuklear Malaysia as a key agency in nuclear science and technology: (1) education and training and (2) technology transfer to industry stakeholders. The Malaysian Government's initiative to leverage nuclear science and technology for social and economic development is supported by international entities such as the International Atomic Energy Agency (IAEA). The IAEA Technical Cooperation Programme has significantly contributed to Malaysia's national infrastructure development, particularly in human capital development. Through this Programme, Malaysia received assistance through fellowships, scientific visits, training, meetings, workshops, provision of experts, and procurement of equipment, which provided a strong foundation for Malaysia to continue sustaining the peaceful uses of nuclear science and technology in national socio-economic development. This paper examines the activities related to promoting science and technology transfer, emphasizing their impact on strengthening the role of science in enhancing the nation's social and economic landscape. For this study, the modified Triple Helix Model is used to interpret the relationship by substituting the role of academia with public research institutions due to their similar functions in fostering science and technology for industrial development. Thus, the model demonstrates how Nuklear Malaysia, as a hybrid organisation, can expand the application of nuclear science and technology for social and economic progress by advancing sectors such as medicine, manufacturing, environment, agriculture, and oil and gas through its scientific innovations. Furthermore, as a hybrid organisation, Nuklear Malaysia plays a crucial role in translating government policies into actionable strategies for relevant industries.